The magnitude optimum tuning of the PID controller: Improving load disturbance rejection by extending the controller - Cvejn, Jan; Vrancic, Damir (My University, 2018)
The Magnitude Optimum (MO) tuning method for PID controllers, applied on stable and non-oscillating plants, usually gives fast tracking responses and offers very good process output disturbance-rejection performance, even if the process contains significant dead time. On the other hand, when an exogenous disturbance affects the process indirectly, for example, via the plant input, slow disturbance rejection responses may be obtained. The paper proposes a way of removing this problem by means of adding two first-order filters into the control loop, without modifying the controller parameters. The filter parameters are determined so that the disturbance lag is partially compensated and the stability margin properties of the MO tuning are preserved.
Metoda optimálního modulu nastavení PID regulátoru: vylepšení potlačení poruchy rozšířením regulátoru
Keywords: PID; process control; disturbance rejection; time delay systems; control systems design; PID; řízení procesů; potlačení poruchy; systémy s časovým zpožděním; návrh řídidicích systémů